Integrasi Kriya Tradisional dalam Desain Fesyen Kontemporer: Kajian Morfologi Estetik dan Keberlanjutan Budaya - Tiara Larissa; Faradillah Nursari; Arini Arumsari; Regina Simamora (PANGGUNG, 2026)
Indonesia’s cultural diversity has produced a wide range of traditional craft techniques, including batik, weaving, embroidery, surface treatments, and natural dyeing, which carry strong aesthetic and cultural values. In contemporary fashion, these techniques are not preserved as static forms but undergo visual transformation to remain relevant to current design contexts and the evolving dynamics of the global fashion industry. This study examines the integration of traditional craft techniques in Indonesian contemporary fashion through an aesthetic morphology approach. Using a qualitative descriptive method, this study conducted a visual content analysis of visual content analysis was conducted on 100 fashion works by five Indonesian designers produced between 2021 and 2024. Thomas Munro’s aesthetic morphology framework was employed to analyze transformations in motifs, scale, surface quality, garment structure, as well as visual organisationorganization, and visual hierarchy. The study concludes that aesthetic morphology provides an effective analytical framework for understanding the visual transformation of traditional crafts and their role in cultural sustainability within contemporary fashion design. These findings demonstrate that adaptive visual strategies enable traditional crafts to function sustainably within evolving global fashion contexts.